Product differentiation and profitability in German manufacturing firms - Nils Braakmann; Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2009)
We use a unique rich newly built data set for German manufacturing enterprises to investigate the product differentiation firm performance relationship. We find that an increase in the degree of product diversification has a negative impact on profitability when observed and unobserved firm characteristics are controlled for. The effects are statistically significant and large from an economic point of view. This helps to understand the at least, at a first glance surprising fact that nearly 40 percent of all manufacturing enterprises with at least 20 employees in Germany are singleproduct firms according to a detailed classification of products, and that multi-product enterprises with a large number of goods are a rare species.
Keywords: D21; L60; 330; Product differentiation; profitability; Germany